Six-week engagement in after-school activities involving chemosensory education does not affect olfactory abilities and personal significance of olfaction in 9-11-year-olds: Preliminary evidence - Martinec Nováková, Lenka; Marková, Magdaléna (Physiology & behavior, 2025)
Chemosensory learning is a lifelong process of acquiring perceptual expertise and semantic knowledge about chemical stimuli within the everyday environment. In the research context, it is usually simulated using olfactory training, which typically involves repeated exposure to a set of odors over a period of time. Following olfactory training, enhanced olfactory performance has been observed in adults, and similar evidence is beginning to emerge in children. However, the literature is scant concerning the effects of interventions that more closely resemble how chemosensory experience is acquired in daily life. Since children's chemosensory ecology appears to play a crucial role in olfactory development, we investigated whether engaging in activities that stimulate the chemical senses enhances olfactory performance and metacognition. To this end, we invited 20 children aged 9-11 years to participate in teacher-assisted after-school activities for 30-60 minutes a day for six weeks. During the odd weeks, the children appraised herbal and spice blends and used them to prepare dishes and make beauty products. During the even ones, they explored the city by smellwalking and created smellscape maps. The educational outcomes were evaluated using the Sniffin' Sticks test for odor identification and discrimination and the Children's Personal Significance of Olfaction. Bayesian analyses did not reveal any compelling evidence in support of the alternative hypothesis that children in the chemosensory education group outperform those in the comparison group at the post-test. Rates of reliable increase but also decrease in performance on the Sniffin' Sticks identification and discrimination tests were similar in both groups. We corroborated the previous findings regarding girls' and older children's greater proficiency at identifying odors and the female keener interest in the sense of smell. We offer several practical suggestions researchers may want to consider to tailor their research protocols to reflect more closely the broader context in which chemosensory learning takes place and better capture the nuanced outcomes of such interventions.
Keywords: Odorants; Olfactory training; Female; dítě; učení; ženské pohlaví; Children; Smell; čichová percepce; Multimodal; Transfer; lidé; Odor; školy; odoranty; Learning; Schools; Olfactory Perception; metakognice; Male; Cognition; Metacognition; Child; mužské pohlaví; čich; Humans